2003
DOI: 10.1016/s0014-5793(03)00230-8
|View full text |Cite
|
Sign up to set email alerts
|

The dual role of protein kinase C in the regulation of telomerase activity in human lymphocytes

Abstract: Protein kinase C (PKC) has been implicated to play an essential function in the upregulation of telomerase activity in activated T cells, yet its role in the regulation of telomerase activity remains largely unknown. In this work, we present evidence that PKC activity is required both for the induction of hTERT expression and for the post-transcriptional control of telomerase enzyme activity in T lymphocytes. Of the several PKC isoforms present in lymphocytes, only the level of PKCj j was greatly increased dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 42 publications
4
25
0
Order By: Relevance
“…PKC-dependent activity was also known to be required in the expression of telomerase activity in activated T lymphocytes [19,20]. In this case, PKC activity was shown to be required both for the induction of hTERT expression and for the post-transcriptional control of telomerase enzyme activity [21]. To further understand the role of PKC-dependent signaling in the expression of telomerase, we have employed U-73122 [22] as an inhibitor for phosphoinositide-specific phospholipase C (PLC) to examine the role of PLC, an up-stream effector of PKC, in the expression of telomerase activity.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…PKC-dependent activity was also known to be required in the expression of telomerase activity in activated T lymphocytes [19,20]. In this case, PKC activity was shown to be required both for the induction of hTERT expression and for the post-transcriptional control of telomerase enzyme activity [21]. To further understand the role of PKC-dependent signaling in the expression of telomerase, we have employed U-73122 [22] as an inhibitor for phosphoinositide-specific phospholipase C (PLC) to examine the role of PLC, an up-stream effector of PKC, in the expression of telomerase activity.…”
Section: Introductionmentioning
confidence: 94%
“…The peripheral blood lymphocytes (PBL) were isolated and cultured as previously described [21]. Cells were grown at 37°C in a humidified incubator containing 5% CO 2 .…”
Section: Cell Culturementioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that telomerase in human breast cancer cells is regulated by PKC a through phosphorylation of hTERT (Li et al, 1998). PKC z has been reported to regulate telomerase activity through both transcription and post-transcriptional mechanisms in nasopharyngeal cancer cells and peripheral T lymphocytes during T-cell activation (Yu et al, 2001;Sheng et al, 2003). These results indicate that telomerase is regulated by various PKC isoenzymes, perhaps depending on the specific cell type or cell status.…”
mentioning
confidence: 95%
“…Studies of protein phosphorylation have indicated that the up-regulation of telomerase activity during megakaryocytic differentiation and T lymphocyte activation is dependent on protein kinase C (PKC) (Counter et al 1998;Sheng et al 2003;Weng et al 1996). PI3K/Akt has also been proposed as a key signaling protein in telomerase regulation (Kawauchi et al 2005).…”
Section: Introductionmentioning
confidence: 99%